Pachyderm Web Site - Birrell, Andrew; Schroeder, Mike; Wobber, Ted (1997)
Pachyderm is a web-based, index-based system for creating, storing and accessing electronic mail and news.
Cached copy of the DEC SRC Pachyderm web site